Virtual Impedance-Based Droop Control Scheme to Avoid Power Quality and Stability Problems in VSI-Dominated Microgrids - Babak Keyvani-Boroujeni (IEEE, 2021)
Droop-based techniques have widely been utilized in controlling voltage source inverter based distributed generation units within a microgrid. Advantages of droop based control have been extensively discussed, while its effects on stability and power quality of the inverter based microgrids have not been explicitly studied. This paper addresses this gap by analyzing the stability of islanded microgrid with focusing on power quality problems. From this viewpoint, current paper studies the effect of parameters change on the stability margin of the microgrid using a bifurcation analysis approach. To this end, this work firstly derives a dynamic model of a microgrid including controllers of the inverter, network and loads. Based on this model, the loci of the system eigenvalues have been analyzed, showing that, by changing the droop coefficients, the hopf and period doubling bifurcation can occur in such a system. Furthermore, the droop tuning procedure may also cause the system to experience the flicker phenomenon in advance of the instability. Next, a virtual impedance-based solution is presented to avoid the flicker as well as instability problems. Finally, the efficacy of the proposed method is proved on a practical network.